(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of open Latarjet procedure for traumatic recurrent anterior shoulder instability in young patients Methods: This descriptive study was conducted in Orthopedics and spine unit Hayatabad Medical Complex Peshawar from 25th January 2018 to 25th December 2021. All adults patients with traumatic recurrent anterior shoulder instability fulfilling the inclusion criteria were treated with open Latarjet Procedure. Functional outcome at two years was assessed with Rowe score and graded as excellent, good, fair and poor. The pre operative and post operative Rowe score was compared and P value calculated with paired sample t test. P value<0.05 was considered significant. Results: We operated 35 patients with open Latarjet procedure. All patients were male. The mean age was 29±4.5 years. Right sided Latarjet was performed in 22(62.85%) patients and left in 13(37.14%). At two years follow up the mean Rowe score improved from pre surgery 39±5.1 to 93.7±6.2. (p<0.05). Excellent functional outcome was reported in 20(57.14%) patients and good in 15 (42.85%) patients. No recurrent instability was noted. Conclusion: Latarjet procedure is a safe and effective treatment option for anterior shoulder instability as excellent and good functional outcome was achieved in majority of our patients.